Trusting on the Edge : Managing Uncertainty and Vulnerability in the Midst of Serious Mental Health Problems - Calnan, Michael; Brown, Patrick (Book collections on Project MUSE., 2012)
This book explores issues central to contemporary theoretical debates around the nature of trust, linking abstract concerns to empirical analysis with interviews with service-users, practitioners and managers.